Penerapan Building Information Modeling (Bim) 5D dalam Perencanaan Ulang Struktur Gedung Rumah Sakit Kasih Ibu Surakarta - Dhanisa Alifia Rachma; Amelia Vista Br Purba; Asri Nurdiana; Bambang Setiabudi (Jurnal Sipil dan Arsitektur, 2025)
The rapid growth of the construction industry necessitates the adoption of Building Information Modeling (BIM) 5D to enhance efficiency, cost accuracy, and scheduling precision. This study focuses on the redesign of the structural system for Kasih Ibu Hospital in Surakarta, located in a seismic-prone zone, using a dual system that combines Special Moment Resisting Frames (SMRF) with shear walls, based on Seismic Risk Category IV and Site Class SD. The planning process utilized Revit 2024 for 3D modeling, ETABS and SP Column for structural analysis, and Microsoft Project for scheduling. The cost estimation was derived from a Quantity Take Off (QTO) integrated with Surakarta’s AHSP unit price database, resulting in a total project value of IDR 83.6 billion including VAT. The structural analysis confirmed compliance with national building codes (SNI 2847:2019, SNI 1726:2019, and SNI 1727:2020), ensuring seismic safety and design efficiency. The BIM 5D integration through Autodesk Navisworks successfully visualized the project’s 3D model, construction timeline, and overall costs over a 43-week implementation period. This study demonstrates that BIM 5D is an effective tool for digitalizing large-scale construction projects in earthquake-prone areas.